Auditoría de gestión y su incidencia en la administración de la cartera de crédito de cooperativa de ahorro y crédito Virgen del Cisne agencia La Maná, año 2014 - Escobar Guilcaso, David Paul (2016)
This research project is developed in the credit union "Virgen del Cisne" dedicated to financial intermediation with products and services for small business. Although the cooperative has very well positioned financial indicators the main problem of the company lies in the Manágement of the loan portfolio is placed in the agency La Manna, the same as has the percentage of delinquencies above permitted , making the level of risk increases, thus greatly it affects the NPLs that Manáges the institution. The main objective of this project focuses on reducing the level of risk that affects the credit Manágement of the cooperative and its Manágement, and serve as a tool for their Manágers in decision-making, increasing control and monitoring processes credit is handled internally. To achieve the above-described primary information obtained by a series of interviews with key representatives of credit and collection area that has the institution in the agency La Manna was collected. The main strength of the company is its infrastructure, because it is adequate and comprehensive offering excellent image to its customers and partners allowing you to have a good reception of the inhabitants of the city making it grow continuously. According to the interview with the principal officers of credit and collection agency La Manna was found that internal policies, manuals functions are fulfilled by 70%, the risks of internal control 14,50%, inherent risk is detected 20% and 10% risk of arrest. Through the development and review of delinquency indicators that shows the cooperative verify that's NPL ratio of 3.09% and percentage of arrears of La Maná is affecting 5.43% and increasing the level of risk, for by last issue a final report that will serve as a tool for credit and collection area to take measures necessary for its eradication.